MODEL KAWASAN AGROWISATA BULO DENGAN MENGGUNAKAN ANALISIS SPASIAL - Hamsah, Hamsah; Nirmawala, Nirmawala; Asrandi, Asrandi; Saleh, Nursahdi (Sekolah Tinggi Pariwisata Ambarrukmo Yogyakarta, 2023)
AbstractNatural resources in the agricultural sector in Bulo District are quite abundant, but they have not been utilized properly. Therefore, there is a need for a special study regarding the implementation of the Bulo District Agrotourism Area based on 3 TBL. This research examines the Agrotourism Area model and how it is implemented to advance the region by implementing the TBL concept in Agrotourism Areas, especially in Bulo District, Polewali Mandar Regency. This TBL concept applies 3 main things, among others [1]: a) A planetary concept that focuses on utilizing the potential that exists in Bulo District to be developed into a sustainable program; b) People concept which focuses on social needs to support improving community welfare; and c) Profit Concept, namely focusing on agrotourism areas to generate profits. The results show that Bulo District has undergone a process towards implementing the TBL concept and after analyzing it using spatial analysis, the results were obtained for an area that has the potential to be used as an Agrotourism Area for Bulo District. Several points that have the potential to be used as agrotourism areas in Bulo District by paying attention to aspects of accessibility, plantation areas, and having large areas are Bulo Botanical Gardens, Ihing Durian Gardens, Uhai Sibali Peak, Senayan Hill, and Lemo Nipi Hill. AbstrakSumberdaya alam dibidang pertanian di Kecamatan Bulo cukup melimpah, hanya saja belum termanfaatkan dengan baik. Olehnya perlu ada kajian khusus tentang Model dan Implementasi Kawasan Agrowisata Kecamatan Bulo dengan mengintegrasikan penggunaan Agriculture Geospatial Information (AGI). Penelitian ini mengkaji tentang model Kawasan agrowisata dan bagaimana implementasinya untuk memajukan daerah dengan mengusung penerapan konsep TBL pada Kawasan Agrowisata khususnya di Kecamatan Bulo Kabupaten Polewali Mandar. Konsep TBL ini menerapkan 3 hal pokok utama antara lain [1]: a) Konsep planet yang fokus dengan memanfaatkan potensi yang ada di Kecamatan Bulo untuk dikembangkan menjadi suatu program yang berkelanjutan; b) Konsep People yang fokus pada kebutuhan sosial untuk mendukung peningkatan kesejahteraan masyarakat; dan c) Konsep Profit yaitu fokus terhadap kawasan agrowisata menghasilkan keuntungan. Hasil menunjukan bahwa Kecamatan Bulo telah mengalami proses menuju penerapan konsep TBL dan setelah dianalisis dengan menggunakan analisis spasial maka diperoleh hasil sebuah area Kawasan yang berpotensi untuk dijadikan Kawasan Agrowisata Kecamatan Bulo. Beberapa titik yang berpotensi untuk dijadikan kawasan agrowisata di Kecamatan Bulo dengan memperhatikan aspek aksesibilitas, area perkebunan, dan memiliki area yang luas adalah Kebun Raya Bulo, Kebun Durian Ihing, Puncak Uhai Sibali, Bukit Senayan, dan Bukit Lemo Nipi.